Investigation on effect of nano gel wollastonite on properties usage of wood-cement composites manufactured from rice straw fibers - Ali Hasanpoor tichi; Behzad Baziyar (تحقیقات علوم چوب و کاغذ ایران, 2018)
In this study the effect of nano gel wollastonite usage in three level (0 , 5 and 10 percent per dry by weight of the cement) and the mixture ratios of lingocellulosic material to cement in three level 10:90, 20:80 and 30:70 on physical, mechanical , microscopic and biological properties of composite made from rice straw fibers- cement was investigated. Three replicates for each treatment and 27 experimental boards were manufactured. Specimens were prepared according to DIN- EN634 standard test methods to measure mechanical and physical properties. Mechanical and physical properties including static bending strength, modulus of elasticity, interior bonding(IB),water absorption after 2 and 24 hours immersion in the water , density and decay resistant (loss weight) were measured. Micro- structural properties of composites were evaluated by SEM images. The results showed that, bending strength , modulus of elasticity , interior bonding and density were significantly increased with increasing Nano gel wollastonite . Also, with increasing Nano gel wollastonite , dimensional stability and decay resistance were increased in comparison with the control sample. Results of scanning electron microscopy showed that the calcium hydroxide formed hydrated calcium silicate gel (C-S-H gel) after addition the Nano gel wollastonite . SEM images showed that the micro- structure of the boards were improved by increasing the nano- wollastonite content.